PENGARUH KECERDASAN EMOSIONAL DALAM PENGAMBILAN KEPUTUSAN (STUDI PADA LURAH PEREMPUAN DI KELURAHAN BANDAR BUAT KECAMATAN LUBUK KILANGAN KOTA PADANG) - Muhammad Takdir; Riswanto Bakhtiar; Jusmita Weriza (UNES Law Review, 2023)
Bandar built village is one of the villages located in the Lubuk Kilangan sub-district, Padang, West Sumatra, Indonesia. Bandar Create Village is also a Village with potential in agriculture, plantations, animal husbandry, and trade in Lubuk Kilangan District, Padang City, West Sumatra Province. Associative causal research methods quantitative techniques. Data collection techniques with questionnaires. The population in this study were all RT, RW in Bandar Create Village, Lubuk Kilangan District, Padang City. With a total of 61 samples that are representative of the existing population. Data analysis used descriptive analysis, classic assumption test, and hypothesis testing. The results showed that the influence on the emotional intelligence variable (X) with Decision Making (Y) was 0.245 or 24.5% while the remaining 20.2% was influenced by other factors not included in this study.